The growth analysis of Harumanis mangoes at Universiti Teknologi MARA, Perlis / Alfi Afzal Mad Yusop - Mad Yusop, Alfi Afzal (2020)
Crop growth and productivity are determined by a wide range of weather, soil and management variables, which vary significantly across space. Growth analysis of Harumanis Mangoes is crucial depend on its productivity and structural significance. This research aims is to map the growth distribution of Harumanis Mangoes in UiTM Perlis and analyse the significant of best farm management practice. The method of positioning has been used and processed by using Geographical Information System (GIS), namely ArcGIS software. The outcomes was established and used to control major location of the observed trees. This research generate map of mangoes tree according to ages variation and growth quality. It was plotted, registered, topologic and analysed. The most immediate analysis is on the growth and its factors distribution in the UiTM area. There area good growth and medium quality growth. The second output is the correlation mapping between growth and the soil series has been found that the Melaka series are the ones that support the most growth of the tree while the Terap Red series do not show a clear indication on the tree growth. The third output is the mapping analysis on the insect affected to the tree growth. There are about 8% of the total tree that are estimated to be at risk of the attack and it was found that all the tree situated 15 metre around are also affected. The study shows that GIS involvement in the agricultural sector can have a better and more manageable impact in supporting a better precise farming practice.